Acceptance, Effectiveness and Relationship of Blended Learning Implementation Among Lecturers in Polytechnic Sultan Mizan Zainal Abidin. - Hasni bin Mahmood; Saupi bin Mohamed Noor (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: This paper aims to analyze Acceptance, Effectiveness and Relationship of Blended Learning Implementation Among Lecturers in Polytechnic Sultan Mizan Zainal Abidin. Design/methodology/approach: The method used is statistic-descriptive and the design used is cross sectional. Findings: 2 hypotheses are rejected while the other is accepted. Research limitations/implications: Variables considered in this study are e-Learning, blended learning, innovation, teaching and online learning. with data showing 270 academic lecturers in PSMZA Practical implications: Results show that from the 2 hypotheses proposed. Originality/value: This paper is original. Paper type: This paper can be categorized as a case study. Keyword: e-Learning, blended learning, innovation, teaching and online learning